Different Phytochemicals, and Their Therapeutic Value of Edible Flowers in Human Health: A Review (International Journal of Food and Nutritional Sciences, 2023)
The consumption of edible flowers promotes new trends in human nutrition. The determination of bioactive component content in their petal's play an important role in estimating their significance as a natural source of antioxidant. Edible flowers can improve the flavour, taste, aroma, visual appeal, and color of food; they have also been used in many remedies and therapeutic formulation. There are a lot of edible flowers are available around the world. Edible flowers are high in phytochemicals (such as phenolic compounds, carotenoids, or terpenoids) that have a number of medicinal effects. Flowers may have been described as food in multiple cultures around the world. Edible flowers contain antioxidant, vitamins, and minerals that contribute to overall well- being to human health. Different flowers have different plant pigment (e.g., Anthocyanin, carotenoids, Chlorophyll, etc.) pigments play a vital role in food colorant as well as food nutrition. Therapeutic potential of edible flowers is: Anti septic, anti- inflammatory, Anti -diabetic, anti-obesity, anti-cancers etc. This review was aimed to study about phytochemical properties of edible flowers. And their therapeutic potential in human health.